Incidence of Venous Thromboembolism by Type of Gynecologic Malignancy and Surgical Modality in the National Surgical Quality Improvement Program. Issue 3 (1st March 2017) - Graul, Ashley; Latif, Nawar; Zhang, Xiaochen; Dean, Lorraine T.; Morgan, Mark; Giuntoli, Robert; Burger, Robert; Kim, Sarah; Ko, Emily
Abstract : Background: Women with gynecologic cancer are at higher risk of venous thromboembolism (VTE) due to malignancy, pelvic surgery, increased age, and frequently comorbidities. The rate of VTE among different gynecologic cancers and relative to benign gynecologic surgeries has not been reported in a nationally representative cohort. Methods: Using the American College of Surgeons National Surgical Quality Improvement Program database, gynecologic surgeries were identified retrospectively from 2006 to 2012. Clinical characteristics, surgical procedures, and 30-day postoperative complications were abstracted. Multivariable logistic regression models were performed. Results: Of all gynecologic surgeries (n = 104, 368), 11, 427 were performed for malignancy: 2.7% (n = 2800) for ovarian cancer, 6.8% (n = 7114) for uterine cancer, 1.0% (n = 1026) for cervical cancer, and 0.5%(n = 487) for vulvar cancer. 202 (1.8%) patients experienced a VTE. Ovarian cancer had a deep venous thrombosis and pulmonary embolism rates of 1.6% and 1.5% compared with uterine cancer, 0.8% and 0.8%, respectively. Ovarian cancer patients were 1.8 (95% confidence interval [CI], 1.19–2.65) times more likely to have a deep venous thrombosis and 1.7 (95% CI, 1.11–2.51) times more likely to have a pulmonary embolism than patients with uterine cancer. Compared with all gynecologic cancer surgeries, ovarian cancer patients were 1.5 times more likely to have a VTE (95% CI, 1.10–2.16). Patients undergoing minimally invasive surgery were 64% less likely to have a VTE regardless of malignancy site; however, if they had disseminated disease, they remained at higher risk of VTE (odds ratio, 5.96; P = 0.027). Conclusions: Of gynecologic cancer surgeries, ovarian cancer patients had the highest rate of VTE. Venous thromboembolism rates were lower in those who had minimally invasive surgery but remained higher in those with disseminated disease.